Citizens of an Enemy State: The Enemy Alien Disability Rule in the Constitution of Nepal - Khati, Prakat; Sharma, Kundan Raj (Kathmandu School of Law Review, 2017)
The Enemy Alien Disability rule has been a constantfeature of many of Nepal’s constitutions in the past and is also featured in its present Constitution. Under this rule, citizens of an enemy state are not protected by the fundamental guarantees of the right to criminal justice and are disabled from seeking constitutional remedies such as a writ of habeas corpus. In this context, a legal and normative analysis of this rule and its compatibility with current norms of Human Rights and of Humanitarian Law is warranted. This article intends to conduct analyses of the historical, normative and legal aspects of this rule.